2019
DOI: 10.3748/wjg.v25.i38.5862
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, work productivity impairment and healthcare resources in inflammatory bowel diseases in Brazil

Abstract: BACKGROUNDInflammatory bowel diseases (IBD) have been associated with a low quality of life (QoL) and a negative impact on work productivity compared to the general population. Information about disease control, patient-reported outcomes (PROs), treatment patterns and use of healthcare resources is relevant to optimizing IBD management.AIMTo describe QoL and work productivity and activity impairment (WPAI), treatment patterns and use of healthcare resources among IBD patients in Brazil.METHODSA multicenter cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 60 publications
1
39
0
7
Order By: Relevance
“…Several studies have shown that IBD strongly impacts work productivity [21,47]. Patients with IBD, significantly younger than those suffering from other chronic diseases, experience an unpleasant condition of work disability, with an increase in unemployment and sick leave and a consequent high socio-economic impact [48]. Social life was negatively influenced by the disease in 74% of the patients in our series and this agrees perfectly with current data showing that up to 75% of IBD patients claimed symptoms which interfere with their ability to enjoy leisure activities [47].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that IBD strongly impacts work productivity [21,47]. Patients with IBD, significantly younger than those suffering from other chronic diseases, experience an unpleasant condition of work disability, with an increase in unemployment and sick leave and a consequent high socio-economic impact [48]. Social life was negatively influenced by the disease in 74% of the patients in our series and this agrees perfectly with current data showing that up to 75% of IBD patients claimed symptoms which interfere with their ability to enjoy leisure activities [47].…”
Section: Discussionmentioning
confidence: 99%
“…Active IBD, especially among CD patients, is associated with a substantial impact on quality of life [ 32 , 33 ]. Curiously, our findings did not differ according to diagnosis (UC or CD) or disease status (active or remission), leading us to believe that the pandemic and its containment measures had an early and negative impact on patients regardless of their IBD phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…15 International studies reported colectomies in 7%-10% of patients with UC, with decreasing colectomy rates over recent years. [16][17][18] Active UC is associated with reduced health-related quality of life (HRQoL) and productivity, [19][20][21][22][23][24] frequent visits to accident and emergency departments (A&E), hospital stays and healthcare costs, [24][25][26] with greater costs with increasing frequency of relapse. 27 Although colectomy may be life-saving, it was recommended not to be considered a cure for UC.…”
Section: Key Messagesmentioning
confidence: 99%